2019
DOI: 10.3390/f10020154
|View full text |Cite
|
Sign up to set email alerts
|

Do Terrestrial Salamanders Indicate Ecosystem Changes in New England Forests?

Abstract: Long-term ecological research (LTER) and monitoring programs accrue invaluable ecological data that inform policy and improve decisions that enable adaptation to and mitigation of environmental changes. There is great interest in identifying ecological indicators that can be monitored easily and effectively to yield reliable data about environmental changes in forested ecosystems. However, the selection, use, and validity of ecological indicators to monitor in LTER programs remain challenging tasks for ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The pair of Burton & Likens' (1975a, 1975b studies have since been cited by hundreds of subsequent studies, some of which argue for the use of P. cinereus as an ecosystem indicator species (e.g. Welsh & Droege, 2001;Siddig, Ochs, & Ellison, 2019), or for the overall importance of plethodontids to terrestrial forest ecosystems (e.g., Davic & Welsh, 2004), and indeed have shaped the thinking of many researchers working on North American plethodontid salamanders since (but see Riedel et al, 2008 andOuellet, 2015 for caution about the use of P. cinereus as an indicator species). Thus, we found it odd that ecosystem ecology was neglected by Petranka (1998), although this seems to be the case for all species accounts throughout the book.…”
Section: (I) Ecosystem Ecologymentioning
confidence: 99%
See 2 more Smart Citations
“…The pair of Burton & Likens' (1975a, 1975b studies have since been cited by hundreds of subsequent studies, some of which argue for the use of P. cinereus as an ecosystem indicator species (e.g. Welsh & Droege, 2001;Siddig, Ochs, & Ellison, 2019), or for the overall importance of plethodontids to terrestrial forest ecosystems (e.g., Davic & Welsh, 2004), and indeed have shaped the thinking of many researchers working on North American plethodontid salamanders since (but see Riedel et al, 2008 andOuellet, 2015 for caution about the use of P. cinereus as an indicator species). Thus, we found it odd that ecosystem ecology was neglected by Petranka (1998), although this seems to be the case for all species accounts throughout the book.…”
Section: (I) Ecosystem Ecologymentioning
confidence: 99%
“…In New York, Beier et al (2012) found a positive relationship between P. cinereus abundance and a well-defined calcium gradient, while in Massachusetts, Ochs & Siddig (2017) found P. cinereus was more prevalent in forests with lower soil pH, lower carbon to nitrogen (C:N) ratios, and lower temperatures. The authors note that the first two characteristics, low soil pH and low C:N ratios, are characteristic of hemlock stands, which used to be much more common within the range of P. cinereus prior to the arrival of hemlock wooly adelgid (Siddig et al, 2019). The loss of hemlocks and other massive ecosystem changes as a result of invasive species who affect fundamental environmental properties relied on by forest floor inhabitants (e.g.…”
Section: (I) Ecosystem Ecologymentioning
confidence: 99%
See 1 more Smart Citation